Differential vulnerability of locus coeruleus and dorsal raphe neurons to chronic methamphetamine-induced degeneration - Du, Yijuan; Choi, Sanghoon; Pilski, Alexander; Graves, Steven M. (Frontiers in Cellular Neuroscience, 2022)
Methamphetamine (meth) increases monoamine oxidase (MAO)-dependent mitochondrial stress in axons of substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) dopamine neurons. Chronic administration of meth results in SNc degeneration and MAO inhibition is neuroprotective whereas the VTA is resistant to degeneration. This differential vulnerability is attributed, at least in part, to the presence of L-type Ca2+ channel-dependent mitochondrial stress in SNc but not VTA dopamine neurons. MAO is also expressed in other monoaminergic neurons such as noradrenergic locus coeruleus (LC) and serotonergic dorsal raphe (DR) neurons. The impact of meth on mitochondrial stress in LC and DR neurons is unknown. In the current study we used a genetically encoded redox biosensor to investigate meth-induced MAO-dependent mitochondrial stress in LC and DR neurons. Similar to SNc and VTA neurons, meth increased MAO-dependent mitochondrial stress in axonal but not somatic compartments of LC norepinephrine and DR serotonin neurons. Chronic meth administration (5 mg/kg; 28-day) resulted in degeneration of LC neurons and MAO inhibition was neuroprotective whereas DR neurons were resistant to degeneration. Activating L-type Ca2+ channels increased mitochondrial stress in LC but not DR axons and inhibiting L-type Ca2+ channels in vivo with isradipine prevented meth-induced LC degeneration. These data suggest that similar to recent findings in SNc and VTA dopamine neurons, the differential vulnerability between LC and DR neurons can be attributed to the presence of L-type Ca2+ channel-dependent mitochondrial stress. Taken together, the present study demonstrates that both meth-induced MAO- and L-type Ca2+ channel-dependent mitochondrial stress are necessary for chronic meth-induced neurodegeneration.